2012
DOI: 10.1371/journal.pone.0035094
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of α9β1 Integrin and VEGF-D Confers Lymphatic Metastatic Ability to a Human Breast Cancer Cell Line MDA-MB-468LN

Abstract: Introduction and ObjectivesLymphatic metastasis is a common occurrence in human breast cancer, mechanisms remaining poorly understood. MDA-MB-468LN (468LN), a variant of the MDA-MB-468GFP (468GFP) human breast cancer cell line, produces extensive lymphatic metastasis in nude mice. 468LN cells differentially express α9β1 integrin, a receptor for lymphangiogenic factors VEGF-C/-D. We explored whether (1) differential production of VEGF-C/-D by 468LN cells provides an autocrine stimulus for cellular motility by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…In an earlier study, utilizing numerous other in vitro assays and tumor xenotransplants in nude mice, we have defined the multiplicity of mechanisms underlying the capacity of the 468LN cells in promoting lymphangiogenesis, lymphovascular invasion and lymphatic metastasis. 8 We showed that they resulted from the dual overexpression of a9b1-integrin and its ligand VEGF-D by 468LN cells. The limitation of the above-mentioned tumor model is that it is time consuming for the xenograft to produce tumors of appreciable sizes to measure intratumoral lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In an earlier study, utilizing numerous other in vitro assays and tumor xenotransplants in nude mice, we have defined the multiplicity of mechanisms underlying the capacity of the 468LN cells in promoting lymphangiogenesis, lymphovascular invasion and lymphatic metastasis. 8 We showed that they resulted from the dual overexpression of a9b1-integrin and its ligand VEGF-D by 468LN cells. The limitation of the above-mentioned tumor model is that it is time consuming for the xenograft to produce tumors of appreciable sizes to measure intratumoral lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…VEGF-D secretion (24 h, in serum-free medium) by these cells were, respectively, 229.50 pg/ml for 468LN and 48.33 pg/ml for DVEGF-D/468LN, measured by ELISA. 8 In the illustrative study, tubes containing BME alone provided the negative control; those with recombinant Using these five types of implants, we quantified both lymphangiogenesis and angiogenesis with indirect and direct measurements in nude mice as outlined in Figure 1 and detailed in methodology. Figure 3 Lymphatic ingrowth assay and mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations